Pengaruh Penggunaan Make Up Wajah Masa Kini Terhadap Tingkat Kepercayaan Diri Pada Kalangan Mahasiswi Universitas Jember - Anakku Saviola; Dava Putratama; Ovie Faiz Pratama; Yohan Eka Wahyunda Febriansyah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Make up is a necessity for women to be able to appear beautiful in social life. Then make up becomes an inseparable aspect of her daily life. By using make-up, women in particular can be more confident in the belief that make-up is a tool for managing good impressions from other people. The purpose of this research is to find out what women do with the use of make-up to be able to receive all good impressions from the public and then how make-up makes them dependent and obsessed with being able to beautify themselves continuously. The method used is a qualitative method, data collection through in-depth interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. This research uses the theory of object feminism from Julia Kristeva. The results of the research show that Jember University students who use make-up have reasons to get an impression from the general public in order to gain an image as a beautiful woman. This happens because of the rejection and discarding of the past that the perpetrators received because they were deemed not to meet existing beauty standards. So that it makes them take action to prove their position so that they can be accepted again and even get a perfect impression.